Necrosis area, Tumor Size, and Lymph Node of Breast Cancer - Laili, Kharima; Pratiwi, Sari Eka; Ilmiawan, Muhammad In'am; Trianto, Heru Fajar; Fitrianingrum, Iit (http://dharmais.co.id/, 2024)
Background: Breast cancer is the leading cause of cancer deaths in women worldwide in 2020. The high mortality rate is often influenced by various reasons, one of which is patients's prognosis. One of the prognostic factors is necrosis area, caused by hypoxic tumor tissue that can affect tumor growth and metastasis. Therefore, this study aims to determine the relationship between necrosis area with tumor size and lymph node metastasis in breast cancer patients. Methods: This study was an observational analytic with a cross-sectional approach. This research was conducted at the Anatomical Pathology Laboratory of Dr Soedarso Pontianak General Hospital and the Microscopy Laboratory of the Faculty of Medicine Tanjungpura University from September until November 2022. The study sample was 55 slides of Formalin-Fixed Paraffin-Embedded (FFPE). The study was conducted by observing the preparations under a microscope and then analyzed using ImageJ and SPSS software. The independent variable in this study was the necrosis area in the tumor microenvironment, and the dependent variables were tumor size and lymph node metastasis in breast tissue. Results: All study samples were female patients with invasive ductal carcinoma. Breast cancer tends to occur in patients aged 48-55 years. The highest percentage of necrosis area was 21% and the most diagnosed breast tumor size and lymph node metastasis were stage T4 and stage N2. Spearman's rho correlation test showed that there was no relationship between necrosis area and tumor size (p = 0.122; r = 0.16) and lymph node metastasis (p = 0.637; r = 0.18). Conclusions: There is no correlation between necrosis area with tumor size and lymph node metastasis of breast cancer patients in the Anatomical Pathology Laboratory at Dr Soedarso Pontianak General Hospital.